Welding Defect Analysis in Low Carbon Steel SMAW Joints Using Visual Inspection and Liquid Penetrant Test as a Basis for Welding Quality Control - Junil Adri; Durain Parmanoan; Andril Arafat; Fadhilah (Jurnal Vokasi Mekanika (VoMek), 2026)
This research is motivated by the importance of the ability of D3 Mechanical Engineering students in evaluating the quality of welded joints, because the welding results that appear unified are not necessarily free from surface defects. This study aims to analyze the types of welding defects in low carbon steel Shielded Metal Arc Welding  joints using Visual Inspection and Liquid Penetrant Test as the basis for welding quality control in vocational learning. The study used a quantitative descriptive design based on applied laboratories involving 48 D3 Mechanical Engineering students divided into three learning sessions. Each student produced one welded joint specimen, so that the total number of specimens analyzed was 48. Data were collected through visual inspection sheets, Liquid Penetrant Test result sheets, photo documentation, and recapitulation of welding defects, then analyzed using frequency, percentage, and technical interpretation of the causes of defects. The results showed that the most dominant defects were porosity with 17 specimens (35.42%), followed by undercut with 14 specimens (29.17%), excessive spatter with 12 specimens (25.00%), and irregular bead with 11 specimens (22.92%). Liquid Penetrant Test detected 64 defect indications, higher than Visual Inspection which detected 49 defect indications. From the quality category, 24 specimens were accepted, 18 required repair, and 6 were rejected. This study concluded that the combination of Visual Inspection and Liquid Penetrant Test is effective for identifying welding defects more comprehensively and can be the basis for quality control of welding learning that is more objective, systematic, and relevant to industrial needs.